2021
DOI: 10.1097/cin.0000000000000803
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Classification of Usability Problems in a Nursing Information System

Abstract: Nursing information system is a system that nurses are required to use in order to perform their daily activities. Poor user interface design of nursing information system can cause problems in nurses' interaction with the system. This research aimed to evaluate the usability of nursing information system. During this study, five evaluators examined the nursing information system with the heuristic evaluation method and by using the checklist of Nielsen usability principles. Then, the identified problems were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Finally, unpleasant interface design can cause challenges in users' interaction with the system [50]. In this study the overall mean score of the interface quality subscale was 3.57 (SD � 1.064), meaning that the majority of the EMS staff rate their interface quality subscale as "useable" at a high level, since a high level interval (3.40-5) as shown in Table 2.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Finally, unpleasant interface design can cause challenges in users' interaction with the system [50]. In this study the overall mean score of the interface quality subscale was 3.57 (SD � 1.064), meaning that the majority of the EMS staff rate their interface quality subscale as "useable" at a high level, since a high level interval (3.40-5) as shown in Table 2.…”
Section: Discussionmentioning
confidence: 64%
“…For example, the participants required the need for clear error messages together with guidance on how to fix them, providing information correlated to common tasks, and improving functions and capabilities of the design to meet the EMS staff's expectations. Earlier research [50,53] has shown that similar modifications can enhance users' interactions with systems.…”
Section: Discussionmentioning
confidence: 99%
“…В охороні здоров'я зручність використання МІС визначається їх зрозумілістю, легкістю у вивченні роботи, легкістю сприйняття, привабливістю, корисністю та потужністю в частині виконання завдань охорони здоров'я. В окремих дослідженнях показано, що протягом останніх двох -трьох десятиліть розробники МІС в окремих країнах провели виражені вдосконалення таких систем для задоволення вимог ЗОЗ та національних систем охорони здоров'я, а також відповідно до запитів та побажань рядових користувачів такого програмного забезпечення [9][10][11].…”
Section: організація медичної допомогиunclassified
“…Multiple technology acceptance theories recognize user experience as key to the adoption of health information technologies (HITs) [ 9 ]. HITs poorly adapted to the work context can cause contradictions to nursing workflows, compromising EHR usability [ 10 ]. Perceived poor EHR usability is associated with a higher level of emotional exhaustion among nurses [ 11 ], hindering system adoption [ 12 ].…”
Section: Introductionmentioning
confidence: 99%